Wet-adhesive and antibacterial PAH-TPP coacervates with self-mineralizing capability for cranial flap fixation - Weicheng Chen; Jiaxu Shi; Dachuan Liu; Kai Lu; Jianlong Fu; Jingxi Xu; Huan Wang; Zhiliang Guo; Li Dong; Di Li; Xin Li; Miodrag J. Lukic; et al. (Bioactive Materials)
Repositioning and securing the cranial bone flap after craniotomy remain significant challenges in neurosurgery. Traditional fixation methods often suffer from weak mechanical strength, bioinertness, limited osteogenic capacity, and a lack of antibacterial properties, complicating clinical outcomes. Recent medical adhesives offer superior fixation but face significant limitations in cranial bone applications. In this study, we explored the application of PAH (Poly (allylamine) hydrochloride)-TPP (Tripolyphosphate) coacervate (PT) as a bone adhesive. The PT coacervate demonstrated excellent anti-swelling (anti-swelling ratio less than 1 %), self-healing, and injectable properties, as well as exceptional shape adaptability and cytocompatibility. Adhesion tests revealed its outstanding adhesion (99.06 ± 11.76 kPa for lap shear and 121.42 ± 16.73 kPa for end to end), long-term durability, and tunable adhesion strength. Furthermore, the coacervate demonstrated broad-spectrum antibacterial activity against both Gram-positive and Gram-negative bacteria (antibacterial rate more than 90 %), with mechanistic studies revealing promising strategies to address localized and systemic drug-resistant infections. Additionally, the coacervate's self-mineralizing properties significantly enhanced its osteogenic performance. In vivo studies confirmed its effective fixation, robust antibacterial activity, and improved osteogenesis, underscoring its suitability for cranial bone flap repositioning and fixation after craniotomy. In summary, this coacervate adhesive offers a promising therapeutic solution for addressing the challenges of cranial flap fixation in neurosurgery.